Boundary Management Permeability and Relationship Satisfaction in Dual-Earner Couples: The Asymmetrical Gender Effect - Russo, Marcello; Ollier-Malaterre, Ariane; Kossek, Ellen Ernst; Ohana, Marc (Frontiers in Psychology, 2018)
Given the increasing use of technology and the growing blurring of the boundaries between the work and nonwork domains, decisions about when to interrupt work for family and vice versa can have critical implications for relationship satisfaction within dual-earner couples. Using a sample of 104 dual-earner couples wherein one of the partners is a member of the largest Italian smartphone-user community, this study examines how variation in boundary management permeability within dual-earner couples relates to partner relationship satisfaction, and whether the effect differed by gender and partners’ agreement on caregiving roles in the family. Using actor–partner analysis, we examined the degree to which an individual and his or her partner’s level of family-interrupting work behaviors (FIWB, e.g., taking a call from the partner while at work) and work-interrupting family behaviors (WIFB, e.g., checking work emails during family dinner) was positively related to relationship satisfaction. Results show that women experienced greater relationship satisfaction than men when their partners engaged in higher levels of FIWB, and this relationship was stronger when partners had perceptual congruence on who is primarily responsible for caregiving arrangements in the family. This study advances research on dual-earner couples by showing the importance of examining boundary management permeability as a family social phenomenon capturing transforming gender roles.